Pengaruh Gaya Belajar terhadap Nilai Bahasa Inggris Siswa - Gita Ramadhani; Sukarman Purba (Journal on Education, 2024)
The learning style is an individual's tendency in how they receive and process information. This study aims to analyze whether there is an influence between learning style variables and students' English language scores. The sample for this research consists of 55 students from the 10th grade of the PSPTV major at SMK Negeri 1 Percut Sei Tuan. Among the participants, 29 students (53%) exhibit a visual learning style, 16 students (29%) an auditory style, and 10 students (18%) a kinesthetic style. The normality test of the data reveals that the visual, auditory, kinesthetic learning styles, and English language scores have a normal distribution. Based on the F-test results, the obtained F-value is 8.378, while the critical F-value for 55 samples is 2.79. It is concluded that both simultaneously and partially, learning styles significantly influence English language scores. Therefore, the null hypothesis (Ho) is rejected, and the alternative hypothesis (Ha) is accepted.